Taxonomic and phylogenetic characterizations reveal two new species and two new records of Roussoella (Roussoellaceae, Pleosporales) from Yunnan, China - Hong Bo Jiang (2019)
© 2019, German Mycological Society and Springer-Verlag GmbH Germany, part of Springer Nature. Roussoella species mainly occur on monocotyledons, especially bamboo, and are characterized by raised, immersed ascostromata, cylindrical to clavate asci and ellipsoidal to fusiform, brown to dark brown, 1-septate, ornamented ascospores. They have cytospora-like asexual morphs with enteroblastic conidiogenous cells and hyaline to dark brown conidia, which are often minutely warty. In this article, two new species and two new records of Roussoella associated with dead bamboo, collected from Yunnan Province of China, are described and illustrated. These four taxa are similar in morphological characteristics, but can be distinguished by phylogenetic analyses of the concatenated ITS, LSU, TEF1-α, and RPB2 sequence data. Based on maximum likelihood and Bayesian inference analyses of the combined sequence dataset, we introduce Roussoella kunmingensis and R. yunnanensis spp. nov. Roussoella mukdahanensis is provided here as the first record on bamboo from China. The asexual morph of R. pseudohysterioides is illustrated and described on dead bamboo culms.